2021
DOI: 10.5588/pha.21.0007
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for poor engagement in drug-resistant TB care in South Africa: a systematic review

Abstract: BACKGROUND: Metrics of poor patient engagement, including missed appointments, treatment interruption, sub-optimal medication adherence, and loss to follow-up, have been linked to poor clinical multidrug-resistant TB (MDR-TB) outcomes. Understanding the risk factors for poor patient engagement is necessary to improve outcomes and control TB. This review synthesizes the risk factors for poor patient engagement in MDR-TB treatment across South Africa.DESIGN: A systematic review of five databases (PubMed, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Then, among recurrent cases from these two countries, the MDR-TB prevalence was 3.9% 17.7% respectively [ 12 ]. In 2019, 23 persons per every 100,000 in the South Africa population were reported to have MDR-TB [ 13 , 14 ]. Regarding risk factors, recent studies conducted in Tanzania and Niger showed TB relapse , history of irregular treatment, cigarette smoking, alcohol abuse, treatment failure, underweight and HIV as leads factors of MDR-TB occurrence [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, among recurrent cases from these two countries, the MDR-TB prevalence was 3.9% 17.7% respectively [ 12 ]. In 2019, 23 persons per every 100,000 in the South Africa population were reported to have MDR-TB [ 13 , 14 ]. Regarding risk factors, recent studies conducted in Tanzania and Niger showed TB relapse , history of irregular treatment, cigarette smoking, alcohol abuse, treatment failure, underweight and HIV as leads factors of MDR-TB occurrence [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a lack of national reporting of adverse events precluded comparisons of toxicity between the two cohorts. We found no evidence that measured patient characteristics shown to be associated with dropout from MDR/RR-TB treatment such as HIV, previous TB treatment, sex, and age [ 23 ], were responsible for the difference by accounting for them in the analysis. However, it is possible other unmeasured factors may be responsible.…”
Section: Discussionmentioning
confidence: 97%
“…Risk factor identification: A critical step in developing effective interventions involves the identification of risk factors associated with poor engagement in MDR-TB care [ 56 ]. Factors such as missed appointments, treatment interruption, sub-optimal medication adherence, and loss of follow-up must be recognized and addressed systematically.…”
Section: Reviewmentioning
confidence: 99%
“…Factors such as missed appointments, treatment interruption, sub-optimal medication adherence, and loss of follow-up must be recognized and addressed systematically. Consistent risk factors, such as male sex and younger age, have been identified as predictors of poor engagement [ 56 ].…”
Section: Reviewmentioning
confidence: 99%